Influência da doença coronariana no risco de sarcopenia em adultos diabéticos tipo 2 acompanhados em um ambulatório de referência - Barroso, Débora da Nóbrega (2024)
Introduction: Diabetes Mellitus 2 (T2DM) is associated with elevated inflammatory cytokines in skeletal muscle tissue that can contribute to muscle loss and reduce muscle strength and function. Glycemic fluctuations that occur in diabetes are considered a greater trigger for oxidative stress than sustained hyperglycemia, inducing greater microvascular complications, which can affect muscle mass, leading to sarcopenia. Macrovascular complications, such as coronary artery disease (CAD) and peripheral vascular diseases, can induce muscle ischemia, muscle weakness, and reduced performance in activities. CAD can directly influence the development and progression of sarcopenia, potentiating factors such as chronic systemic inflammation and endothelial dysfunction. Furthermore, when associated with diabetes, CAD can potentiate these processes by increasing muscle catabolism and promoting sarcopenia, leading to accelerated functional decline, greater frailty, and increased mortality. Objective: To analyze the influence of coronary heart disease on the risk of sarcopenia in diabetic adults followed at a diabetes referral outpatient clinic. Methods: This is a cross-sectional, analytical observational study carried out from March 2023 to March 2024. A total of 161 adults diagnosed with type 2 diabetes mellitus (T2DM) were included, according to the criteria established by the American Diabetes Association, regardless of gender, who were undergoing outpatient treatment for diabetes with or without CAD. An assessment questionnaire was initially applied to collect sociodemographic data and data regarding health condition (disease duration). The algorithm proposed by the Revised European Working Group on Sarcopenia in Older People (EWGSOP2) was used to find, assess, confirm, and establish the severity of sarcopenia. Results: Of the 161 participants, 67 (41.6%) had only T2DM and 94 (58.4%) had CAD associated with T2DM. The groups were homogeneous regarding demographic and clinical characteristics. We observed that individuals at risk of sarcopenia were older (p=0.013), thinner (p<0.001), with lower BMI (p=0.005), with a longer time since diagnosis of T2DM (p<0.001), 87.2% had glycated hemoglobin (HbA1c) greater than 7% (p<0.001) and 76.9% had CAD associated with T2DM (p<0.001). Individuals with confirmed sarcopenia, according to the algorithm proposed by EWGSOP2 were thinner (p<0.001), had a lower BMI (p=0.001), a longer time since T2DM diagnosis (p=0.001), and 90% had HbA1c greater than 7% (p=0.032). However, no significant difference was observed in the presence of CAD. In addition, logistic regression indicated that HbA1c>7% (OR 5.8, 95% CI 2.3-14.6, p<0.001), more years since diagnosis of T2DM (OR 1.12, 95% CI 1.05-1.19, p<0.001) and having CAD (OR 5.5, 95% CI 2.3- 12.8, p<0.001) significantly increase the patient's risk of having sarcopenia. Conclusion: The time of diagnosis of T2DM, glycated hemoglobin levels above 7% and the presence of CAD associated with T2DM are the main risk factors associated with sarcopenia in diabetic individuals.